HSPA1L and HSPA1B gene polymorphisms and haplotypes are associated with idiopathic male infertility in Iranian population. (September 2019) - Kohan, Leila; Tabiee, Omid; Sepahi, Neda
Abstract: Objective: Male infertility is a multifactorial disease resulting from the interaction between the genetic and environmental factors. Spermatogenic failure accounts for more than half of male infertility cases. Heat shock proteins (HSPs) are the molecular chaperones that are involved in different developmental stages of spermatogenesis. The current study was planned to investigate the role of HSPA1L rs2227956 and HSPA1B rs1061581 gene polymorphisms in idiopathic male infertility. Study Design: This case-control study was conducted on 516 subjects consisted of 308 patients with idiopathic male infertility and 208 age matched-(±5) control subjects. HSPA1L rs2227956 and HSPA1B rs1061581 polymorphisms were genotyped by PCR-RFLP method. Results: A significant association with male infertility was found for HSPA1L rs2227956 in genotypes (TT vs CT: OR = 2.049, 95% CI = 1.337–3.139, P = 0.001; TT vs CC: OR = 3.028, 95% CI = 1.100–8.332, P = 0.032). In the dominant genetic model, rs2227956C allele increased the risk of male infertility (OR = 2.049, 95% CI = 1.337–3.139, P = 0.001). Also, the results showed a significant association between the HSPA1B rs1061581GG genotype and male infertility (OR = 2.638, 95% CI: 1.001–4.486, P = 0.001). The rs1061581 G allele was a risk factor for male infertility (OR = 1.657, 95% CI = 1.278–2.148, P < 0.001). Haplotype analysis showed CG and TA (rs2227956/ rs1061581) haplotype affect the risk of male infertility (P < 0.001). Conclusion: HSPA1L rs2227956 and HSPA1B rs1061581 gene polymorphisms are associated with susceptibility to idiopathic male infertility in Iranian population. Further studies in different ethnicity are necessary to confirm these results.